2009
DOI: 10.1111/j.1551-2916.2009.03028.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Ba/Ti Ratio on the Microstructures and Dielectric Properties of Barium Titanate‐Based Glass–Ceramics

Abstract: A series of BaTiO 3 (BT)-based ferroelectric glass-ceramics have been prepared via controlled crystallization by varying the Ba/Ti ratio in an aluminum silicate glass composition, and the subsequent microstructure, phase evolution, and dielectric properties have been investigated. X-ray diffraction indicated that an increasing Ba/Ti ratio promoted the crystallization of BaTiO 3 and BaAl 2 Si 2 O 8 from the glass matrix, and the cracking of glass-ceramics appears to be correlated to mismatch in the thermal expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(41 citation statements)
references
References 16 publications
0
41
0
Order By: Relevance
“…An endothermic peak and two exothermic peaks were observed in the DSC patterns, which was corresponded to the temperature of glass transition and crystallizations. The first exothermic peak (T p1 ) was the crystallization temperature of the perovskite phase (BST) [10], while the secondary exothermic peak (T p2 , 1,010°C) corresponded to the crystallization of Ba 2 Al 2 Si 2 O 8 , SrAl 4 O 7 and SiO 2 [4,11,12]. When the content of La 2 O 3 increased to 0.5 wt%, the T p2 increased slightly.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…An endothermic peak and two exothermic peaks were observed in the DSC patterns, which was corresponded to the temperature of glass transition and crystallizations. The first exothermic peak (T p1 ) was the crystallization temperature of the perovskite phase (BST) [10], while the secondary exothermic peak (T p2 , 1,010°C) corresponded to the crystallization of Ba 2 Al 2 Si 2 O 8 , SrAl 4 O 7 and SiO 2 [4,11,12]. When the content of La 2 O 3 increased to 0.5 wt%, the T p2 increased slightly.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, it is very important to increase the BDS to improve the energy-storage density. In contrast to the conventional powder-processed ferroelectric ceramics, glass-ceramics, fabricated through controlled nucleation and crystallization, possess uniform microstructure and have little porosity, which provide unique attribution for energystorage applications [4].…”
Section: Introductionmentioning
confidence: 99%
“…Glass-ceramic dielectrics, which are prepared by first obtaining a glass matrix by melt casting and then precipitating a crystal phase in the glass matrix during subsequent heat treatment, have been considered as a more attractive candidate in the fields of high-voltage and high energy density applications. In contrast to conventional ceramics, glass-ceramic dielectrics have high dielectric constant (from the precipitated ceramic phases) and high breakdown strength E b (from the near pore-free inherence of the residual glass) [5][6][7][8]. Generally, the energy storage density for dielectric capacitors is proportional to the dielectric constant ε r and the square power of the applied electric field E 2 (EoE b , E b is the breakdown strength), so the glass-ceramic dielectrics possess the potential to achieve a much higher energy storage density.…”
Section: Introductionmentioning
confidence: 98%
“…However, the lattice parameters of the perovskite phase were hardly changed, which had been calculated and were listed in Table 1. It was suggested that the constituents of Kaolinite did not work as dopants incorporating into the perovskite lattice but reacted with part of [16][17][18] locating at triple points, which was supported by the SEM-EDX evidences (see Fig. 3).…”
Section: Tablementioning
confidence: 95%